Emerging medicines to improve the basic defect in cystic fibrosis. (3rd July 2022) - Fajac, Isabelle; Sermet-Gaudelus, Isabelle
ABSTRACT: Introduction: Cystic fibrosis (CF) is a severe autosomal recessive disorder featuring exocrine pancreatic insufficiency and bronchiectasis. It is caused by mutations in the cystic fibrosis transmembrane conductance regulator gene ( CFTR ) encoding the CFTR protein, which is an anion channel. CF treatment has long been based only on intensive symptomatic treatment. During the last 10 years, new drugs called CFTR modulators aiming at restoring the CFTR protein function have become available, and they will benefit around 80% of patients with CF. However, more than 10% of CFTR mutations do not produce any CFTR protein for CFTR modulators to act upon. Areas covered: The development of CFTR modulators and their effectiveness in patients with CF will be reviewed. Then, the different strategies to treat patients bearing mutations non-responsive to CFTR modulators will be covered. They comprise DNA- and RNA-based therapies, readthrough agents for nonsense mutations, and cell-based therapies. Expert Opinion: CF disease has changed tremendously since the advent of CFTR modulators. For mutations that are not amenable to CFTR modulators, new approaches that are being developed benefit from advances in molecular therapy, but many challenges will have to be solved before they can be safely translated to patients.